Relationship Between Metacognitive Skills and Information Processing Skills Among Al-Quds University Students - Rimawi, Omar; Rimawi, Amira (European Scientific Journal, ESJ, 2020)
Metacognitive skills and information processing are key concepts in the field of education, they are crucial in the learning process. The present study aimed to identify the relationship between metacognitive skills and information processing skills among the students of Al-Quds University. The study instruments were applied on a sample of 393 male and female students. The results showed that there was a positive correlation between metacognitive skills and information processing among Al-Quds University students. The findings revealed statistically significant differences in the level of metacognitive skills, attributed to gender in favor of female students. However, there were no statistically significant differences due to faculty or academic level. The findings also showed that there were no statistically significant differences in the level of information processing skills attributable to gender and academic level. However, there were statistically significant differences in the level of information processing due to the faculty variable in favor of the Faculty of Science.